An enantioselective organocatalytic intramolecular Morita–Baylis–Hillman (IMBH) reaction of dienones, and elaboration of the IMBH adducts to fluorenones. Issue 57 (3rd July 2017) - Satpathi, Bishnupada; Wagulde, Siddhant V.; Ramasastry, S. S. V.
Abstract : An efficient synthesis of cyclopenta-fused arenes and heteroarenes has been achieved via an enantioselective organocatalytic intramolecular Morita–Baylis–Hillman (IMBH) reaction of dienones. The IMBH-adducts were transformed to fluorenones in a serendipitous manner. Abstract : An enantioselective organocatalytic intramolecular Morita–Baylis–Hillman (IMBH) reaction of dienones is reported for the first time. This has been achieved by incorporating entropy and synergy considerations during the substrate design. The reaction conditions are thoroughly verified for an efficient synthesis of highly functionalised cyclopenta-fused arenes and heteroarenes in excellent yields and enantioselectivities. The synthetic utility of the IMBH-adducts has been demonstrated by transforming them into 3, 4-disubstituted fluorenones in a serendipitous manner.